Ambient climate and soil effects on the headspace under clear mulch film. (February 2016) - Lisson, S.N.; Tarbath, M.; Corkrey, R.; Pinkard, E.A.; Laycock, B.; Howden, S.M.; Botwright Acuña, T.; Makin, A.
Abstract: Clear degradable mulch film (CDMF), when installed over a newly sown crop, fundamentally alters the growing environment through the entrapment of heat and CO2, the attenuation of incident solar radiation and, the capture and return of evapotranspiration losses back to the soil. These changes can be harnessed by farmers in a variety of ways to increase crop production through, for example, earlier sowing and more rapid crop establishment, reduced frost risk, geographical expansion of a crop into new areas otherwise unsuited to that crop, and soil water conservation in low rainfall areas. Conversely, when used at the wrong time of year, the temperatures under the film can reach levels that result in plant heat stress. This paper reports on an investigation conducted in southeast Tasmania into how key headspace climate variables (daily maximum and minimum temperatures, relative humidity, total daily radiation and atmospheric CO2 concentration) under CDMF respond to changing ambient climatic conditions and underlying soil characteristics. The film fundamentally altered the growing environment with incident solar radiation reduced by up to 34%, daily maximum temperatures reaching a peak of 60 °C, daily minimum temperatures up to 20 °C above ambient levels in summer and, atmospheric CO2 concentrations up to 100 times ambient levels. The magnitude of these responses was all sensitive to soil type. Simple models were derived for predicting daily headspace solar radiation, maximum temperature and minimum temperature from readily available ambient data. These models can be used to identify site-specific, operational limits for film application and, when integrated into farm system models, enable the prediction of wider production and environmental impacts under film. Highlights: This paper reports on the effects of clear mulch film on the growing climate. The film attenuates incident solar radiation by up to 26% Daily maximum temperatures reached a peak of 60 °C and daily minimum temperatures up to 20 °C above ambient levels in summer CO2 entrapment resulted in atmospheric concentrations up to 100 times ambient levels Simple models were derived for predicting headspace maximum and minimum temperatures and radiation from ambient climate equivalents and daylength.